1998
DOI: 10.1002/(sici)1097-010x(19981015)282:3<290::aid-jez2>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulation and salinity effects on the expression and activity of Na+,K+-ATPase in the gills of European sea bass,Dicentrarchus labrax (L.)

Abstract: The European sea bass, Dicentrarchus labrax, tolerates salinities ranging from freshwater (FW) to hypersaline conditions. In two experiments, we analysed changes in plasma ions, muscle water content (MWC), gill Na+,K+‐ATPase activity, and α‐subunit mRNA expression during the course of acclimation from 15 ppt salt water to FW or high salinity seawater (HSSW). In Experiment 1, fish (6.2 ± 1.1 g) were acclimated from 15 ppt to either FW, 5, 15, 25, 50, or 60 ppt SW and sampled after 10 days. Gill Na+,K+‐ATPase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
107
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(135 citation statements)
references
References 51 publications
25
107
3
Order By: Relevance
“…The results also fell within the range reported for other marine/estuarine teleosts (e.g., Maren et al, 1992;Claiborne et al, 1994;Zadunaisky et al, 1995;Zadunaisky, 1996;Jensen et al, 1998;Marshall et al, 1999). When facing salinity changes, plasma osmolality and chloride concentrations directly reflect the fishes capacity of extracellular fluid homeostasis.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The results also fell within the range reported for other marine/estuarine teleosts (e.g., Maren et al, 1992;Claiborne et al, 1994;Zadunaisky et al, 1995;Zadunaisky, 1996;Jensen et al, 1998;Marshall et al, 1999). When facing salinity changes, plasma osmolality and chloride concentrations directly reflect the fishes capacity of extracellular fluid homeostasis.…”
Section: Discussionsupporting
confidence: 73%
“…Actually it is possible that either to hypo-regulate in full-strength seawater, or to hyper-regulate in dilute seawater both require increased levels of branchial ATP supply ("U-shaped" curves, e.g. Stuenkel & Hillyard, 1980;Jensen et al, 1998;Imsland et al, 2003;Lin et al, 2004;Laiz-Carrión et al, 2005). Another possibility is that structural changes such as covering the apical pits of chloride cells turns off salt secretion, as reported for estuarine fish facing reduced salinities (Sakamoto et al, 2000;Daborn et al, 2001;Marshall, 2003), thus preventing the need to increase ATPase consumption and the activation of energy-consuming processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• C. Response of gill Na + -K + ATPase activity to environmental salinity could be categorized in two principal groups: (1) a direct relationship which is characteristic of anadromous species, in which higher salinities induce higher values of gill Na + -K + ATPase activity (McCormick 1995) and (2) a U-shaped relationship, described for some euryhaline teleosts (Towle et al 1977;Gallis et al 1979;Jensen et al 1998), in which lower values of gill Na + -K + ATPase activity occur at isotonic environments and higher values at low and high salinities. It was expected that Na + -K + ATPase activity would be lowest in isotonic media as there are fewer ion fluxes, but unexpectedly a direct linear relationship between environmental salinity and Na + -K + ATPase was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Only minor meristic and morphological phenotypic differences necessitating detailed studies to be identified exist in sea bass, and their interaction with fitness is unknown (Barnabé 1973, Corti et al 1996, Loy et al 1999, Bahri-Sfar and Ben Hassine 2009, Costa et al 2010. Concurrently, sea bass has repeatedly demonstrated different capabilities to acclimate freshwater (FW) in both experimental and natural conditions (Chervinski 1974, Dendrinos and Thorpe 1985, Cataudella et al 1991, Venturini et al 1992, Allegrucci et al 1994, Marino et al 1994, Jensen et al 1998, Eroldogan and Kumlu 2002, Varsamos et al 2002, Nebel et al 2005, Boutet et al 2007, GiffardMena et al 2008, Dufour et al 2009. Sea bass could then be a mixture of cryptic phenotypes with distinct environmental tolerance and fitness regarding salinity, rather than a single unconditional, plastic, euryhaline phenotype as traditionally reported in textbooks (Pickett andPawson 1994, Sánchez Vázquez andMuñoz-Cueto 2014).…”
Section: Introductionmentioning
confidence: 99%